Ultrasound Therapy and Towel Exercise to Increase Ankle Rom and Functional Activity in Plantar Fascitis - Aryani Hasan, Nabila Fajrin; Hermawan, Agung (Universitas Pekalongan, 2024)
Introduction: Plantar fasciitis occurs due to excessive activity such as standing or walking for a long time and causes micro injury to the plantar fascia muscle which experiences constant stretching repeatedly The purpose of this study was to determine the effect of physiotherapy management on plantar fasciitis with ultrasound therapy and towel exercise modalities. Method: this research using descriptive analytic methods, the therapy was carried out 5 times. Result: there was an increased range of motion from T1: S = 10º-0º-40º to T5: S = 15º-0º-45º. Increased functional activity from T1: 45% to T5: 51%. conclusion: The conclusions from this study are increased range of motion of the ankle joint and functional activity in the ankle.